-7-5(6-m)=-43+5m

Simple and best practice solution for -7-5(6-m)=-43+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-5(6-m)=-43+5m equation:


Simplifying
-7 + -5(6 + -1m) = -43 + 5m
-7 + (6 * -5 + -1m * -5) = -43 + 5m
-7 + (-30 + 5m) = -43 + 5m

Combine like terms: -7 + -30 = -37
-37 + 5m = -43 + 5m

Add '-5m' to each side of the equation.
-37 + 5m + -5m = -43 + 5m + -5m

Combine like terms: 5m + -5m = 0
-37 + 0 = -43 + 5m + -5m
-37 = -43 + 5m + -5m

Combine like terms: 5m + -5m = 0
-37 = -43 + 0
-37 = -43

Solving
-37 = -43

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x^2+3-23=0 | | x+61=80+x+55 | | 2x+4x=(5-3y) | | Z=(2-3j)+(5-4j^3) | | 8(n+4)=10(n-10)-2n | | 5x+4=10x | | 2x+4x(5-3y)= | | 30x-5y=40 | | 3(w+2)-5w= | | 9x+6-3x=6+5x+9 | | .5x+.333x+63=30 | | -3(x-6)=-4+5 | | 9(y-3)=7+8y | | z^2-(3-2i)z+(5-i)=0 | | 13/6=-1 | | 80+55=x+51 | | (1-3y+8)=(2+6-4) | | 2x-3=3(x+9) | | 2[w-(4w+20)+12]=2(w+8) | | 9(k+1)-(-7k-7)=15k | | 80+55=53+x | | 6(x+-6)-8(x+2)=-10 | | 5(x)=(2x-2)(m+6) | | 2cosx-sinx=5/4 | | (X^2+9x-3)(X^2+6x-5)= | | 9-(4y-3)=2-5y | | 6x+13-4x+13=-6 | | 8x+3y=-33 | | 10x-2(2x-2)=5x+1 | | 2x/3-5=x/2-3 | | 4-5x=3x+20 | | ((7a^2b^3c^0)/(3a^3b^4c^3))^-4 |

Equations solver categories